Pendampingan Kewirausahaan Mahasiswa di Highland Roastery dan Rumah Kopi Jayapura pada Masa Covid-19 - Tanan, Christina Irwati; Boari, Yoseb; Binur, Resini Handayani Eklefina (LP2M INSURI Ponorogo, 2022)
Student Entrepreneurship Assistance at the Highland Roastery and Jayapura Coffee House is an effort of the UOGP Development Economics Study Program to increase the entrepreneurial spirit of students and foster student entrepreneurship interest as a skill to create jobs when they graduate. The method in student mentoring activities is the first stage of preparing student entrepreneurship activities, secondly implementing student entrepreneurship activities, assisting in making reports on student entrepreneurship activities, and fourth evaluating student entrepreneurship mentoring activities. This student entrepreneurship activity was carried out during the Covid-19 period so that students could find out about the problems and efforts made by Business Partners to overcome the impact of Covid-19 Pendampingan kewirausahaan mahasiswa di Highland Roastery dan Rumah Kopi Jayapura sebagai upaya Program Studi Ekonomi Pembangunan UOGP untuk meningkatkan jiwa kewirausahaan dan menumbuhkan minat kewirausahaan mahasiswa untuk menciptakan lapangan pekerjaan setelah mereka lulus. Metode dalam kegiatan pendampingan mahasiswa dilakukan dengan beberapa tahapan. Pertama, persiapan kegiatan kewirausahaan mahasiswa. Kedua, pelaksanaan kegiatan kewirausahaan mahasiswa. Ketiga, pendampingan pembuatan laporan kegiatan kewirausahaan mahasiswa. Keempat. evaluasi kegiatan pendampingan kewirausahaan mahasiswa. Kegiatan kewirausahaan mahasiswa ini dilakukan pada masa Covid-19 sehingga mahasiswa dapat mengetahui masalah dan upaya yang dilakukan mitra bisnis untuk mengatasi dampak Covid-19.